2005
DOI: 10.1159/000087731
|View full text |Cite
|
Sign up to set email alerts
|

Cells on a Chip - the Use of Electric Properties for Highly Sensitive Monitoring of Blood-Derived Factors Involved in Angiotensin II Type 1 Receptor Signalling

Abstract: Background: We developed a highly sensitive cardiomyocyte based screening system for the non-destructive electronic detection of chronotropic drugs and tissue-secreted factors involved in AT1 receptor-mediated cardiovascular diseases. Methods: For this purpose we cultured spontaneously beating neonatal rat cardiomyocytes on microelectrode arrays (MEAs), and tested the optimised, stable culture parameters for a reproducible real-time recording of alterations in contraction frequency. After the evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Temperature is a crucial parameter for electrically excitable cells. A previous study demonstrated a linear correlation between increasing temperature and contraction frequency of cardiac myocytes [Rothermel et al, 2005], which is in good agreement with our findings. To exclude thermal effects, all exposure experiments were performed using a temperature controller to maintain the temperature at 37 8C.…”
Section: Discussionsupporting
confidence: 94%
“…Temperature is a crucial parameter for electrically excitable cells. A previous study demonstrated a linear correlation between increasing temperature and contraction frequency of cardiac myocytes [Rothermel et al, 2005], which is in good agreement with our findings. To exclude thermal effects, all exposure experiments were performed using a temperature controller to maintain the temperature at 37 8C.…”
Section: Discussionsupporting
confidence: 94%
“…For immunolabeling, MCF-7 cells were fixed with 4% formaldehyde for 30 min at room temperature. Immunofluorescence labeling was carried out as previously described (14). The rabbit polyclonal primary antibody anti-occludin (Santa Cruz Biotechnology, Santa Cruz, CA, USA) was used at a concentration of 1 g/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Among others, the cardiomyocyte biosensor based micro-sensors were used for counting contractions by extracellular recording of field potential. Therefore, angiotensin II, the ligand of the AT1 receptor with a positive chronotropic activity, was detected at very low concentrations of 10 211 M. At the interface of micro-sensor system technology and cellular bioengineering, a multi-microelectrode array (MMEA) has been designed for the real time screening of cardiomyocyte ischemia in real time and online (31).…”
Section: Nanotechnology Development and Applicationmentioning
confidence: 99%
“…Thus, the presented technique can be of great benefit for the pharmaceutical industry, especially in respect of functional lead identification, the developing of individualized therapies and safe drug development processes. These assays in combination with the outstanding quality of materials constitute the basis for constant analysis of the cells in vitro and may as well support quality control of industrial bioprocesses, biotechnology,and pharmacy (31,36,37). Innovations like laser nanoelectricbeam surely can improve the precision of the measurements with focus on single cell analysis (37).…”
Section: Nanotechnology Development and Applicationmentioning
confidence: 99%